Analisis Kinerja Guru Dalam Mengembangkan Bahan Ajar IPS Terpadu Kelas VIII di SMPN 7 Medan - Budiyanti Budiyanti; Nazwa Aulia Azhari; Muhammad Najmul Fahmi; Ellma Aggresia Br Purba; Aprilia Zaeni Rapiah; Dhea Zuhrika; Agustina Rahayu Sianturi; Siti Nurhaliza Lubis; Dra Tumiar Sidauruk (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research analyzes teacher performance in developing Integrated Social Sciences teaching materials at SMPN 7 Medan. The research method used is a qualitative descriptive method. The interview results show that teachers are able to organize teaching material by combining various fields of study, such as Geography, Economics, History and Sociology, by agreeing on a theme first before presenting it to students. The development of Geography teaching materials, which is considered more difficult than other fields of study, is carried out with a longer time allocation and the use of local resources. In teaching methods, teachers apply fun approaches such as discussion, Contextual Teaching Learning (CTL), Quantum Teaching, and inquiry to increase student involvement and encourage critical thinking. However, obstacles in developing teaching materials, especially Geography material, are overcome by enriching literacy and utilizing learning methods based on group discussions and case studies. Integrated social studies learning at SMPN 7 Medan becomes more effective and relevant to students' daily lives thanks to the contextual approach applied by the teacher.